2010
DOI: 10.1021/jm100380k
|View full text |Cite
|
Sign up to set email alerts
|

Glucosylated Deferiprone and Its Brain Uptake: Implications for Developing Glucosylated Hydroxypyridinone Analogues Intended to Cross the Blood−Brain Barrier

Abstract: This report presents that Deferiprone, the only clinically used 3-hydroxypyridin-4-one (HPO), is able to penetrate the blood-brain barrier (BBB) in guinea pigs, whereas its glucosylated analogue is unable to do so. This finding is contrary to published information suggesting that the glucosylation of HPOs is a viable means of enhancing the brain uptake of this group of compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…In its mass spectrum, the molecular ion peak was noticed m/z at 254. To make an evaluation of the antiviral properties of 2-substituted methlthio-5-(4-amino-2-methylpyrimidin-5-yl)-1,3,4-thiadiazole (9a-9v), the bioassays against TMV have been carried out according to the halfleaf juice-robbing method, with the commercial plat virucide Ningnanmycin used as the control [29]. The antiviral assay (curative, protection, and inactivation) results of all compounds were listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In its mass spectrum, the molecular ion peak was noticed m/z at 254. To make an evaluation of the antiviral properties of 2-substituted methlthio-5-(4-amino-2-methylpyrimidin-5-yl)-1,3,4-thiadiazole (9a-9v), the bioassays against TMV have been carried out according to the halfleaf juice-robbing method, with the commercial plat virucide Ningnanmycin used as the control [29]. The antiviral assay (curative, protection, and inactivation) results of all compounds were listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…To make an evaluation of the antiviral properties of 2‐substituted methlthio‐5‐(4‐amino‐2‐methylpyrimidin‐5‐yl)‐1,3,4‐thiadiazole ( 9a , 9b , 9c , 9d , 9e , 9f , 9g , 9h , 9i , 9j , 9k , 9l , 9m , 9n , 9o , 9p , 9q , 9r , 9s , 9t , 9u , 9v ), the bioassays against TMV have been carried out according to the half‐leaf juice‐robbing method, with the commercial plat virucide Ningnanmycin used as the control . The antiviral assay (curative, protection, and inactivation) results of all compounds were listed in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Cognitive improvements were reported for two executive functions [193] while Phase II trials are underway for HD [194]. Investigators have demonstrated that though Deferiprone (61) can enter the brain at low concentration [196] and reduce iron content [197], it is prone to rapid metabolism in the liver [198]. 24, 61) has been clinically approved as a therapy for iron overload and close analogs, designed to overcome its intrinsic metabolically liability, have been reported.…”
Section: Iron Chelation Therapiesmentioning
confidence: 99%
“…And it could redistribute iron within cells, e.g., remove labile iron in mitochondria (Sohn et al, 2008), which could facilitate the management of iron within cells such as those in deep gray matter in MS. In the future, access of chelators to the brain will likely improve as recent studies have investigated ways to increase their permeability into the brain (Roy et al, 2010; Ma et al, 2012; Liddell et al, 2013). …”
Section: Chelation In Multiple Sclerosismentioning
confidence: 99%